Analisis Implementasi Pembelajaran Berbasis Teknologi Informasi - Wahyuni Nadar (PEDAGOGIKA, 2020)
This research was conducted to describe the results of the analysis of the implementation of IT-based learning at the Bunga Bangsa Kindergarten Islamic School Bekasi. This analysis includes understanding the concept of IT-based learning implemented at the Bunga Bangsa Islamic School Kindergarten, knowing the obstacles in the implementation of IT-based learning at the Bunga Bangsa Kindergarten Islamic School Bekasi and describing the strategies carried out in implementing IT learning at the Bunga Bangsa Islamic School Kindergarten. This research was conducted for 3 months with a qualitative descriptive approach. Data collection is done by interviews, observation and analysis of documents in the form of curriculum documents, RPPH learning planning and assessment of children's learning outcomes and documentation of the use of IT tools used in learning. Data analysis begins by describing the findings of the study and then conducts an objective discussion with a theoretical approach. In this study, the learning process was described in the Bunga Bangsa Islamic School Kindergarten and the use of technological tools in various aspects of learning components such as media, learning resources and also as learning support. The learning process is more interesting and not monotonous, thus creating a fun and interactive atmosphere. The constraints found were that there was still a lack of teacher references to using IT tools in learning associated with activities in the theme and the lack of teachers' skills in using existing IT tools. Current efforts to overcome these obstacles are by providing various references in the form of videos, books and workshops on the use of IT in learning.